Ornamental use of Guarianthe skinneri (Orchidaceae), in Chiapas and Guatemala, is partially responsible for its diversity and genetic structure - Coutiño-Cortés, Ana Gabriela; Bertolini, Vincenzo; Archila Morales, Fredy; Valle-Mora, Javier; Iracheta-Donjuan, Leobardo; García-Bautista, Maricela; Ruiz-Montoya, Lorena (Instituto de Ecología, A.C., 2018)
Background and Aims: Guarianthe skinneri is a native orchid from Chiapas, Mexico, with a Central American distribution, which is threatened by extraction and illegal trade. For this reason, it is classified as threatened in the Mexican rule NOM-059-SEMARNAT-2010. In the region of Soconusco (Chiapas, Mexico) and Guatemala, it is commonly called “Candelaria”, because its flowering time coincides with the dates of the virgin of the same name. In Tapachula city (Chiapas, Mexico), it is common to find plants of this species in the courtyards of private gardens. The objective of this work was to estimate the diversity and genetic structure of G. skinneri from samples obtained from an urban population of Tapachula and from its comparison with five wild populations of Guatemala, in order to determine the potential of the urban population as a source of propagules and understand if genetic distance between populations could be related with the geographic distance that separates them.Methods: Nucleotidic variation in sequences of two regions of ribosomal nuclear DNA (ITS 1-2 and ITS 3-4) was used as genetic marker. The sequences were concatenated obtaining the conventional parameters of diversity and genetic structure.Key results: We observed populations with low and high genetic diversity. A total of 38 haplotypes were observed, whose number per population was between 1 and 15. Haplotidic diversity (Hd) was between 0 and 1, the average number of polymorphic sites was between 0 and 165. The nucleotidic diversity (p) and the average number of nucleotidic differences shows that Tapachula had the greatest diversity, followed by populations of Guatemala. The genetic structure was moderate (Fst=0.083) and the genetic distance was not associated with the geographic distance of the populations.Conclusions: The diversity patterns and genetic structure between populations were attributed to anthropogenic factors derived from its ornamental use, especially in the city of Tapachula.